Second primary tumors of head and neck: review of theories explaining their formation and the newest terminology - Giefing, Maciej; Wierzbicka, Małgorzata; Szyfter, Krzysztof (Contemporary Oncology/Współczesna Onkologia, 2004)
The recurrence and second primary tumors (SPT) are often the reason why the therapy of head and neck squamous cell carcinoma fails. In recent years a regular increase in the SPT occurrence was observed, which turned out it to be an important clinical problem, because the percentage of survivals for patients who developed second primary tumors drops dramatically compared to the patients with the index tumor only. The 5-year survival rate in patients with SPT varies from 8% to 12%. The second primary tumor causes 71% of deaths whereas the index tumor only 15%. The most recent research in the fields of molecular biology and genetics gives an insight into the mechanism according to which these tumors develop and can improve the diagnosis and maybe also the curability. This article reviews all important theories dealing with the process of field cancerization and second primary tumors development. The already classic theory of field cancerization introduced by Slaughter is presented and also more recent theories originating from Slaughter’s concept. The debate on the mechanism of second primary tumors development is not only theoretical because every theory implies a different therapy. Additionally, the newest terminology introduced in the recent publications that has not been yet widely used in the Polish literature is presented. The implementation of the terminology in Poland is aimed to order and standardize the nomenclature used.